Autoimmune gastritis pathogenesis and risk factors of stomach malignant neoplasia - Ye. A. Losik; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate possible pathways of development of stomach malignant neoplasias at autoimmune gastritis.Key points. Stomach cancer traditionally occupies one of the first places within oncologic diseases in the world. Nowadays some factors, increasing its risk are revealed. They include mucosal atrophy and presence of foci of metaplasia. Thus, it is possible to consider autoimmune gastritis as disease which natural course can lead to premalignant lesions of the stomach mucosa. Development of carcinoid tumor deriving from enterochromaffin-like cells (ECL-cells) is typical for type A gastritis. Gradual development of stomach corpus atrophy and respective reductionof parietal cells number causes final development of hypergastrinemia. Excessive amount of gastrin, in turn, stimulates ECL-cells and can result in their hyperplasia and dysplasia. Development of adenocarcinoma is preceded by structural mucosal changes: atrophy and metaplasia that result from inflammatory changes at autoimmune gastritis. At the presence of accompanying H. pyloriinfection eradication therapy is strongly recommended today for reduction of neoplasia risk.Conclusion. One of the primary goals within framework of cancer-prevention and early diagnostics of neoplastic diseases is duly diagnostics of autoimmune gastritis and selection of groups of patients with high risk of stomach cancer for constant out-patient monitoring.